Investigation on the relationship between power nap and cognitive performances among night shift workers - Nur Hosnafartini, binti Safei (Universiti Malaysia Sarawak, (UNIMAS), 2017)
Increasing in industrial related accidents that occurred during night shift work has led to this research that focusing on the ways to overcome the accidents that may happen. The purpose of this study is to investigate the differences between power napping and non-power napping on cognitive performances of night shift workers. The independent variables of this study are the presence of power nap, capability to adapt night shift and age groups of the participants while the dependent variable is cognitive performance of the workers. The study utilized an experimental methodology, then the findings were analysed by using SPSS. This study was carried out among 12 auxiliary police in Universiti Malaysia Sarawak (UNIMAS). In the Coglab assessments, there were several cognitive performances that have been measured which were memory, attention and perception. The results of the finding showed there is no significant difference between power napping and non-power napping on cognitive performance of night shift workers, there is no significant difference between the participants’ age and cognitive performance and there is no significant relationship of capability to adapt night shift and cognitive performance.